Farmers' knowledge and perceptions on fruit flies and willingness to pay for a fruit fly integrated pest management strategy in Gamo Gofa zone, Ethiopia. Issue 2 (4th March 2021) - Muriithi, Beatrice W.; Gathogo, Nancy; Rwomushana, Ivan; Diiro, Gracious; Mohamed Faris, Samira; Khamis, Fathiya; Tanga, Chrysantus; Ekesi, Sunday
ABSTRACT: Bactrocera dorsalis (Hendel) is one of the most economically important invasive pests affecting horticulture production in sub-Saharan Africa (SSA). Mango is the main host for this species and causes up to 80% yield loss. To mitigate against this pest, an area-wide integrated pest management (IPM) programme is being promoted in SSA, and Ethiopia is next in line for roll-out. The IPM strategy reduces pesticide use and generates significant income. However, implementation of the IPM requires significant time investment for pest identification, scouting, certain infrastructure, creating awareness and training for area-wide adoption. To assess farmers' knowledge and perceptions of B. dorsalis and their willingness to pay (WTP) for the IPM, 365 households were interviewed in two mango producing districts in Goma Gofa zone in Ethiopia. A logistic regression model was used to analyse responses to a double-bounded contingent valuation survey. The results showed that 47% of the respondents are WTP for the IPM strategy. Average WTP per hectare was estimated at US 134, revealing an existing demand for fruit fly IPM. The respondents' WTP for the strategy was driven by farm and socio-economic characteristics. Enhancing skills of extension agents could foster IPM dissemination and adoption among mango growers in this region.